2015
DOI: 10.1186/s12879-015-0939-3
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to switch to doxycycline from azithromycin for treating genital chlamydial infections in women? Modelling the impact of autoinoculation from the gastrointestinal tract to the genital tract

Abstract: BackgroundSingle-dose azithromycin is recommended over multi-dose doxycycline as treatment for chlamydial infection. However, even with imperfect adherence, doxycycline is more effective in treating genital and rectal infection. Recently, it has been suggested that autoinoculation from the rectum to the genitals may be a source of persistent chlamydial infection in women. We estimated the impact autoinoculation may have on azithromycin and doxycycline effectiveness.MethodsWe estimate treatment effectiveness us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…However, C. trachomatis has been transmitted sexually among humans, forcing C. trachomatis to adapt to the human genital mucosa and allowing the cytotoxin genes to be lost or significantly shortened in C. trachomatis (49). Nevertheless, C. trachomatis has been frequently detected in the GI tract in humans but without any significant association with GI pathologies (14)(15)(16)(17)50). C. trachomatis may have experienced selection pressures from both the genital and GI tracts.…”
Section: Discussionmentioning
confidence: 99%
“…However, C. trachomatis has been transmitted sexually among humans, forcing C. trachomatis to adapt to the human genital mucosa and allowing the cytotoxin genes to be lost or significantly shortened in C. trachomatis (49). Nevertheless, C. trachomatis has been frequently detected in the GI tract in humans but without any significant association with GI pathologies (14)(15)(16)(17)50). C. trachomatis may have experienced selection pressures from both the genital and GI tracts.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Gratix, et al 18 reported that when CT testing was expanded to include evaluation of rectal swabs, case detection for CT increased by 44%, leading them to support universal screening of women attending STI clinics.…”
Section: Discussionmentioning
confidence: 99%
“…C. trachomatis is frequently detected in human GI tracts (29)(30)(31)(32)51) and can infect human enteroendocrine cells (52). Women practicing oral or anal sex could introduce C. trachomatis into their GI tracts (30,32), while those not practicing these behaviors were also found positive for C. trachomatis in their rectal swabs (29,31), suggesting that C. trachomatis may spread from women's genital tracts to the GI tracts via sexual behavior-independent pathways, as shown in mice (36).…”
Section: Discussionmentioning
confidence: 99%